A pragmatic analysis of addressing terms in a Javanese chronicle, Babad Banjoemas Wirjaadmadjan - Sari, Rosdiana Puspita; Hadiati, Chusni; Muttaqin, Usep (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
Addressing term is a common language phenomenon as it functions as a linguistic unit to refer to someone in a conversation whether it is the speaker, the hearer or the object being discussed. Addressing terms are also found in a chronicle, a written historical record, of a certain place, person, or events. Babad Banjoemas Wirjaatmadjan (BBW) exhibited the history of Banyumas, a regency in the southern part of Central Java. It was written by Raden Wirjaatmadja and continued by Raden Poerwasoepradja. As this paper uses a pragmatic approach, context is significant in the analysis. The context of Banyumas culture is essential in revealing the function of each addressing term used in the chronicle. By using descriptive qualitative methods, the analysis shows that addressing terms in BBW are used to show formality, to show politeness, to show social status, to show inferiority, to show power and to refer to inanimate objects. There is no clear boundary among those functions as similar addressing terms can be used in various conte